P120 Detection of syphilis and other pathogens associated with genital lesions using plexpcr. (8th June 2017) - Erskine, Simon; Windsor, Madeline; Njuguna, Peter; Tucker, Rachel; Wee, Rachel; Tan, Litty; Azzato, Franca; Mokany, Elisa
Abstract : Introduction: Syphilis is an STI caused by the bacterium Treponema pallidum that can result in substantial morbidity and mortality. Recently, there has been an alarming global resurgence of syphilis with infections rising to unprecedented rates. As such, it is increasingly pertinent to test genital lesions for syphilis. Moreover, Herpes simplex virus types 1 and 2 (HSV–1 and HSV–2) and Varicella zoster virus (VZV) cause lesions in cutaneous and mucocutaneous sites. Recent publications have found VZV in genital specimens, suggesting that reactivation of VZV in this atypical presentation is not as uncommon as previously believed, further necessitating the importance of identifying these organisms at these sites. Methods: The PlexPCR HSV-1&2, VZV, Syphilis test (SpeeDx) is a single-well multiplex qPCR for testing genital lesions for the targets HSV-1, HSV-2, VZV and T. pallidium . The performance of the assay was evaluated on 90 genital specimens for which in-house PCR results for syphilis had been determined. Results: The multiplexed assay detected 54/57 syphilis positives, corresponding to a sensitivity and specificity of 94.7% and 100.0%, respectively. The assay also detected four HSV–1 and two HSV–2 infections (2 and 1 syphilis co-infections, respectively). All assays demonstrated analytical sensitivity to 10 copies per assay. Discussion: The lesion assay offers simultaneous detection and differentiation of pathogens that cause genital lesions. In response to the current emerging syphilis outbreak, this assay could provide a rapid and effective method of determining the infectious agent responsible for genital lesions, supporting earlier detection and rapid treatment to reduce morbidity or worse outcomes.